A Metastable Aluminosilica Compound for Aluminum and Water Transport to the Upper Mantle - Frans J. M. Rietmeijer; Joseph A. Nuth (International Journal of Geophysics)
It has been suggested that crystalline “phase egg,” AlSiO3OH, with a ratio Al/Si=1 could carry aluminum and water to the mantle but its natural occurrences are still speculative. An amorphous phase with a fixed and unique, deep metastable eutectic Al2Si2O7 composition was produced in laboratory experiments wherein conditions favored kinetically controlled formation of amorphous solids. This experimentally produced kaolinite-dehydroxylate is highly reactive and it is proposed as the precursor of phase egg in subducting slabs of crustal rocks. If so, metastable phases play a role in subduction zones and it then follows that the processes and resulting conditions in these environments can be nonuniform and discontinuous at least at micrometer scales.